PENGEMBANGAN MEDIA PODCAST TERHADAP KEPERCAYAAN DIRI SISWA SMP MUTIARA 4 BANDUNG - Nafitrian Azhari; Wahyu Hidayat; Maya Masyita Suherman (IKIP Siliwangi, 2023)
The development of podcasts on the self-confidence of SMP Mutiara 4 Bandung students is a new innovation in guidance and counseling service activities using media that keep up with the times. The indicator of self-confidence according to the theorist, namely Lauster, becomes an urgency for students in the future. This study uses research and development methods by Borg and Gall which aims to produce products that have been tested by several validators, namely material experts, media experts, and practitioners. The research subjects consisted of 10 students for the limited trial, and 20 students for the wide trial, all of them were students of SMP Mutiara 4 Bandung who had problems in self-confidence. Based on the results of product testing by several validators, this podcast has an average percentage of 93.19% which according to predetermined criteria that the product is very suitable for use without revision. The results of observations and interviews with teachers and students showed high enthusiasm for the development of this podcast and the students had the ability to increase their understanding of self-confidence after conducting guidance and counseling activities using this podcasts. Keywords: Media, Podcast, Self Confidence.